Estilos de liderazgo de los directores desde la percepción de los docentes de las instituciones educativas estatales de la Red N° 8 - Callao - Escandón Borja, Alicia (2012)
The research had the purpose of identifying the educational perception of the styles of the directors' of the net leadership Nº 8. Their design is of descriptive simple type, the sample that you employment was constituted by 119 professors of educational institutions that have the level of secondary education, The evaluation instrument it was the Questionnaire of Styles of Leadership of Castro (2004). You has arrived to the following results: The predominant leadership in the educational institutions is the transactional leadership with an average of 3.22; Laissez faire leadership in educational institutions occupies a low presence with an average of 2.01; the leadership transformacional is the one that I occupy less level in the scale in the educational institutions with an average of 2.51, being concluded that the predominant styles of leadership are the transformacional and the transactional one, and some directive practice the leadership Laissez Faire.